Aplikasi Konsentrasi Asap Cair Terhadap Pertumbuhan Dan Produksi Bebagai Varietas Padi (Oryza sativa L.) - Ana Amiroh; Crisna Prabowo; Istiqomah Istiqomah; Choirul Anam; Mariyatul Qibtiyah; Dian Kusumawati (Paspalum: Jurnal Ilmiah Pertanian, 2022)
Rice is a staple food source for most of the population of Indonesia and Asia. However, rice production has decreased over time due to the conversion of agriculture into industrial or residential areas. One strategy to increase production is to use high-yielding varieties and improve the cultivation system. Liquid smoke is one solution to neutralize acidity and maintain soil quality. This study aimed to test the effect of liquid smoke concentration on the growth and production of several rice varieties. This research was conducted in Plangwot village, Laren sub-district, Lamongan regency, in March - June 2021. The data analysis method used factorial randomized block design (RAK). The first factor is the variety of rice and the second factor is the concentration of liquid smoke. The results showed that each variety gave the best results at different concentrations of liquid smoke. The best treatment was found in the Inari 42 variety with a concentration of 2% liquid smoke, the Inari 32 variety with a 4% concentration, and the Ciherang varieties with a concentration of 2% and 4%. There is a tendency that increasing the concentration of liquid smoke to 4% results in a decrease in the growth and production of rice plants.